1999
DOI: 10.1021/bi9830213
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of mRNA Cap Analogues as Inhibitors of in Vitro Translation

Abstract: Fifty-eight analogues of the 5'-terminal 7-methylguanosine-containing cap of eukaryotic messenger RNA were synthesized and tested for their ability to inhibit in vitro protein synthesis. A new algorithm was developed for extracting KI, the dissociation constant for the cap analogue.eIF4E complex, from protein synthesis data. The results indicated that addition of a methyl group to the N2 of guanine produced more inhibitory compounds, but addition of a second methyl group to N2 decreased the level of inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 69 publications
6
123
1
Order By: Relevance
“…There is some concern that if an RNA has a TMG cap instead of an m7G cap, this could have repercussions for the initiation of translation. The proportion of hypermethylated guanosine-capped RNAs was found to be lower in polysomal RNA than in nonpolysomal RNA, suggesting that TMG RNAs may not be translated efficiently (57,58). How these in vitro findings reflect in vivo translation is not entirely clear, however.…”
Section: Discussionmentioning
confidence: 97%
“…There is some concern that if an RNA has a TMG cap instead of an m7G cap, this could have repercussions for the initiation of translation. The proportion of hypermethylated guanosine-capped RNAs was found to be lower in polysomal RNA than in nonpolysomal RNA, suggesting that TMG RNAs may not be translated efficiently (57,58). How these in vitro findings reflect in vivo translation is not entirely clear, however.…”
Section: Discussionmentioning
confidence: 97%
“…Unlike eIF4E, N and VP39 bind m 7 GDP or m 7 GMP with a similar weak affinity, suggesting that the triphosphate moiety of the terminal cap does not play a major role during binding. However, the role of triphosphate moiety in the binding of cap with eIF4E is well understood (55)(56)(57). Previous studies have also reported that nucleotides adjacent to the 5Ј cap affect the cap binding with eIF4E, CBP, and VP39 in a different manner.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this explanation, the GpppG analogue, which is unable to bind eIF4E, and cannot induce conformational changes, does not alter eIF4E nuclear body morphology. 14,85,88 The GpppG analogue is also unable to alter PML-NB morphology. However, unlike eIF4E, PML protein is unable to directly bind the m 7 GpppG cap analogue.…”
Section: Spotlightmentioning
confidence: 99%